(untitled) (Biodiversitas Journal of Biological Diversity, 2014)
Ravanbakhsh M, Amini T, Hosseini SMN. 2015. Plant species diversity among ecological species groups in the Caspian Sea coastal sand dune; Case study: Guilan Province, North of Iran. Biodiversitas 16: 16-21. Biodiversity is often discussed in terms of species diversity is concentrated. Species diversity is one of the important characteristics of biological communities and its as a function of the number and size represent populations of species in a special geographic region.The aim of this study was to identification of ecological species groups and investigates the diversity among ecological species groups. The research area comprises a coastal dune system in northern of Guilan Province, Iran. Vegetation sampling was carried out along 22 shore perpendicular transects, approximately 500-m long. A total of 62 plot of 25 square meters were taken in transects. In each sampled plot, the cover percentage value of each species was estimated using Bran-Blanquet scales. Vegetation classified using Two-Way Indicator Species Analysis (TWINSPAN). The comparison of diversity indices among groups were performed with ANOVA test. The results revealed that there were 232 plant taxa and 8 ecological species group in the region. Results of analysis of variance in species diversity indices showed significant differences among the groups in terms of biodiversity indices. The survey of variation in the groups showed that groups 5 and 6 had the highest and groups 1, 2, 3, and 7 had the lowest indices. Checking of the group’s position with high diversity in comparison with other groups in this coastal area indicates that the group settled on the coastal land with stabilized soil and proper distance from the sea had higher diversity indices.